Optimized anisotropic magnetoelectric response of Fe61.6Co16.4Si10.8B11.2/PVDF/Fe61.6Co16.4Si10.8B11.2 laminates for AC/DC magnetic field sensing. (20th April 2016) - Reis, S; Silva, M P; Castro, N; Correia, V; Gutierrez, J; Lasheras, A; Lanceros-Mendez, S; Martins, P
Abstract: The anisotropic magnetoelectric (ME) effect on a Fe61.6 Co16.4 Si10.8 B11.2 /PVDF Fe61.6 Co16.4 Si10.8 B11.2 laminate composite has been used for the development of a magnetic field sensor able to detect both the magnitude and direction of AC and DC magnetic fields. The accuracy (99% for both AC and DC sensors), linearity (92% for the DC sensor and 99% for the AC sensor) and reproducibility (99% for both sensors) indicate the suitability of the sensor for applications. Furthermore, the sensitivity of the Fe61.6 Co16.4 Si10.8 B11.2 /PVDF/Fe61.6 Co16.4 Si10.8 B11.2 anisotropic magnetic sensor—15 and 1400 mV Oe −1 for the DC and AC fields, respectively—are the highest reported in the literature for polymer-based ME materials. Such features, combined with its flexibility, versatility, light weight, low cost and low-temperature fabrication, lead to the suitability of the developed sensor for use in magnetic sensor applications.